2015
DOI: 10.1159/000371510
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Insulin-Like Growth Factor 1 Is Associated with Cognitive Impairment in Parkinson's Disease

Abstract: Objective: The aim of this study was to test plasma insulin-like growth factor 1 (IGF-1) change in Parkinson's disease (PD) and essential tremor (ET), and assess the association of plasma IGF-1 level with motor and nonmotor symptoms in PD and ET. Methods: Plasma IGF-1 was measured in 100 PD patients, 40 ET patients, and 76 healthy controls. Motor and nonmotor symptoms were assessed by different scales. Spearman correlation test and linear logistic model were used to analyze the correlation of plasma IGF-1 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…A similar finding has been recently reported by another group [12], where the reduced IGF-1 receptor is only associated with Lewy bodies disease, but not PD. Given the PD cases used for current study were not Lewy body disease the changes of IGF-1 function may be the hallmark for PD with dementia [28]. Interestingly, the activation of IGF-1R was in close correlation with cell proliferation in capillaries, in which these proliferating cells were highly associated with the pericytes (Figure 4).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A similar finding has been recently reported by another group [12], where the reduced IGF-1 receptor is only associated with Lewy bodies disease, but not PD. Given the PD cases used for current study were not Lewy body disease the changes of IGF-1 function may be the hallmark for PD with dementia [28]. Interestingly, the activation of IGF-1R was in close correlation with cell proliferation in capillaries, in which these proliferating cells were highly associated with the pericytes (Figure 4).…”
Section: Discussionmentioning
confidence: 91%
“…IGF-1 deficiency has been reported in PD patients by showing increased plasma IGF-1 and IGF binding protein (IGFBP)-3 [28]. While over 75% of circulating IGFBPs are IGFBP-3 [29], the dominant binding protein in the CNS is IGFBP-2 [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of recent studies mainly focus on plasma IGF-1 levels as a biomarker for PD progression. Several groups published studies suggesting IGF-1 levels were increased in the sera of PD patients compared to control 188, 189 . Furthermore, studies revealed that increased plasma IGF-1 levels correlate with cognitive decline and motor symptoms 188, 190 .…”
Section: Iis Signaling and Mn In Other Nddsmentioning
confidence: 99%
“…Several groups published studies suggesting IGF-1 levels were increased in the sera of PD patients compared to control 188, 189 . Furthermore, studies revealed that increased plasma IGF-1 levels correlate with cognitive decline and motor symptoms 188, 190 . While these studies have great utility as a clinical tool and seem to be quite sensitive, they have added minimal mechanistic insight as to if or why IGF-1/insulin and related signaling may be dysregulated or pathogenic consequences.…”
Section: Iis Signaling and Mn In Other Nddsmentioning
confidence: 99%